Analisis Faktor-faktor yang Mempengaruhi Perilaku Pembelian Kompulsif di Pusat Perbelanjaan: Studi Kasus pada Indomaret dan Alfamart di Kabupaten Bantul - Utami, Yuli (Jurnal EMT KITA, 2024)
This study aims to investigate the impact of income, age, gender, and education level on compulsive buying behavior in shopping centers in Bantul Regency, Yogyakarta Special Region Province, with a focus on Indomaret and Alfamart stores. A total of 200 consumer respondents who met the criteria, namely having made purchases 3 times, were selected using convenience sampling. Data collection was carried out through questionnaires, and data analysis used statistical equipment. The research results show that of the four variables tested as determinants of compulsive buying behavior, only sex (gender) has a significant influence on this behavior. In contrast, income, age, and education level could not be identified as differentiating factors for compulsive buying behavior. It is known that only age has a significant effect on compulsive buying behavior, while income, gender, and education level do not have a significant impact on compulsive buying behavior at Indomaret and Alfamart shopping centers.